Nearpod use as a learning platform to improve student learning motivation in an elementary school - Muhammad Ilyas Abdullah; Dian Inayati; Ninik Nurlaila Karyawati (Journal of Education and Learning (EduLearn), 2022)
Education sector is heavily affected by COVID-19 pandemic, leading to reduced learning motivation among students. Factors including incondusive learning environment, stress, and anxiety are believed to be the reasons of students’ lower motivation among students. This study investigated the use of Nearpod in an elementary school to improve student learning motivation during online learning. In this qualitative experimental research with thematic analysis, three classes with a total of 46 students and three teachers were participating for one week. The results of the study showed that gamification and interactivity of Nearpod help build up and develop students’ learning interests, leading to greater attention, engagement, and improvement of student attendance rates. Some suggestions on how to effectively integrate gamification in learning are postulated.